Minusca on its Mandate - Setyawati, Amelia; Risman, Helda; D.W, Surryanto (Technium Social Sciences Journal, 2020)
Since independence from France in 1960, the Central African Republic (CAR) has never been free from conflict. Almost every turn of CAR leader begins with a coup d’etat. Resistance from the Seleka and Anti-Balaka rebel groups emerged and exacerbated the situation in CAR. The conflict that was originally an opposition-government conflict developed into a religious conflict. So the question arises regarding the efforts and involvement of third parties in maintaining peace in the CAR. The UN Security Council permits the spread of UN peacekeeping operations through The UN Multidimensional Integrated Stabilization in the Central African Republic (MINUSCA) on 10 April 2014 by protecting civilians as a top priority. The focus of this article is to analyze MINUSCA in carrying out its mandate in CAR. This article is analyzed with role theory and conflict theory. The data used in analyzing this article is secondary data. The data is obtained from books, scientific journals, dissertations or theses, official documents, and the internet. The results in this article find that the role played by MINUSCA in the CAR Conflict is as a peace facilitator. While carrying out their duties, MINUSCA plays a role in the protection of CAR civilians and the development of troop personnel in order to increase the effectiveness of missions in the CAR in order to create a peaceful and safe environment.